Digitalisasi Manajemen Pengetahuan Model SECI untuk Tata Kelola Badan Usaha Milik Desa: Studi Kasus di Kabupaten Bintan - Sophia, Uly; P. Lubis, Djuara; Soetarto, Endriatmo; Retno Hapsari, Dwi; Sarwoprasodjo, Sarwititi (Jurnal Riset Komunikasi (JURKOM), 2025)
Digital transformation represents a crucial strategy for strengthening knowledge governance in community-based organizations, particularly Village-Owned Enterprises (BUMDes). SECI Model Knowledge Management serves as an important framework for enhancing BUMDes governance capacity. This study analyzes the opportunities and challenges of digitalizing BUMDes knowledge systems using the SECI Model in Bintan Regency, Riau Islands Province. The research methodology employed a descriptive qualitative case study approach focusing on BUMDes Mitra Perdana (Teluk Sasah Village) and BUMDes Hilir Sehati (Hilir Village). Data were collected through in-depth interviews with BUMDes officials and stakeholders, then analyzed using Nvivo 12 plus. Results indicate that digitalization opens opportunities for improving governance efficiency, financial transparency, and community empowerment. BUMDes Mitra Perdana demonstrates greater innovation with its Pertashop unit and rental business, while Hilir Sehati focuses on accommodation services and savings-loan programs. This research contributes to communication strategy of knowledge management literature by proposing community-based communication strategies in frontier, outermost, and border villages.